A decade of Hubble Space Telescope science : proceedings of the Space Telescope Science Institute Symposium, held in Baltimore, Maryland, April 11-14, 2000 - Livio, Mario, 1945-; Noll, Keith S.; Stiavelli, Massimo (Space Telescope Science Institute symposium series ;, 2003)
The Hubble Space Telescope has made some of the most dramatic discoveries in the history of astronomy. From its vantage point 600km above the Earth, Hubble is able to capture images and spectra that would be difficult or impossible to obtain from the ground. This volume represents some of the most important scientific achievements of the Hubble Space Telescope in its first decade of operation. Written by world experts, the book covers topics ranging from our own solar system to cosmology. Chapters describe cutting edge discoveries in the study of Mars and Jupiter, of stellar birth and death, of star clusters, of the interstellar medium, of our own Milky Way Galaxy and of other galaxies, of supermassive black holes, and of the determination of cosmological parameters, including the age and ultimate fate of our universe. This is an indispensable collection of review articles for researchers and graduate students.